(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. Il profilo soggettivo: la confessione Chiesa d’Inghilterra - 3. I contenuti: un’analisi genealogica - 4. (segue) la carenza di specificità - 5. Spunti conclusivi. The Agreement between the Italian State and the Church of England. A Genealogy ABSTRACT: On 30 July 2019, the Church of England signed an Agreement with the Italian State pursuant to art. 8, last paragraph, of the Italian Constitution. The Agreement is the first following Sentence no. 52 of 2016 by the Italian Constitutional Court, a judgement which was highly criticized by the doctrine as it gave too few attentions to concrete problems which affect minority denominations. As expected, the Agreement presents the same flaws of the previous ones to which is actually similar. More precisely, it seems to borrow entire articles from them, simply making systematic adjustments of the provisions. For these reasons, it seems possible to make ‘a genealogy’ of it in order to detect the juridical roots of its content and, therefore, a sort of evolution in the process of standardization. The operation seems to reveal a progressive loss of relevance of the negotiations on content, as the sole purpose of the Agreements seems to be to grant to denominational parties the set of privileges consolidated over time.